2016
DOI: 10.1186/s12957-016-0800-1
|View full text |Cite
|
Sign up to set email alerts
|

Results of optimal debulking surgery with bowel resection in patients with advanced ovarian cancer

Abstract: BackgroundThe surgical treatment of patients with advanced-stage ovarian cancer is based on maximal cytoreduction with widening the debulking on the extra-ovarian tissues and infiltrated organs. The purpose of the study was to assess the outcome after optimal cytoreduction with partial bowel resection and to find the risk factors of relapse. Another goal was the quantitative and qualitative assessment of intra- and postoperative complications in the studied group.MethodsThe analysis of debulking procedures wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Another study reported that 87% of patients undergoing primary debulking surgery were indicated for bowel surgery . To date, many studies have reported that surgical resection of the involved bowel is feasible with an acceptable complication rate and is related to a survival benefit . However, there are few reports about the extent or number of resections in bowel surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study reported that 87% of patients undergoing primary debulking surgery were indicated for bowel surgery . To date, many studies have reported that surgical resection of the involved bowel is feasible with an acceptable complication rate and is related to a survival benefit . However, there are few reports about the extent or number of resections in bowel surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…As ovarian cancer often presents in the advanced stage and frequently involves the small and large bowels, bowel surgery has been a crucial part of debulking procedures . Several studies have reported that surgical resection of the involved bowel is feasible with an acceptable complication rate and is related to a survival benefit . To achieve optimal debulking, extensive bowel resection including multiple bowel resection or subtotal colectomy is sometimes warranted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whenever the surgical team decides to perform a low rectosigmoidian resection with anastomosis, the surgeon should take into consideration the fact that in this context the risk of anastomotic dehiscence remains one of the most frequent and serious complications, ranging between 0.8 and 6.8% (21,22). In the meantime, the factors contributing to a higher risk of anastomotic leaks consist of a higher length of operative time, a higher need of blood transfusion and a shorter length of the distal anastomotic partner (2). Whenever one of these situations are encountered, performing a diverting ileostomy or even a Hartmann procedure might be performed in order to minimize the risk of a life-threatening complication such as an anastomotic leak.…”
Section: Discussionmentioning
confidence: 99%
“…Background Ovarian cancer is a common malignancy encountered in women worldwide, presenting an increasing incidence in the last decades. Among European women it is estimated that the incidence of ovarian cancer reached 4% of all malignancies, being in the meantime the sixth cause of cancer related death (1,2). This fact is mainly related to the high capacity of spread of the malignant process via multiple pathways, leading to the apparition of disseminated lesions at the time of diagnosis.…”
mentioning
confidence: 99%